Pengaruh Kompensasi, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Pemerintah Daerah (Studi Kasus di DPPKAD Kabupaten Karanganyar) - Sudradjat, Eko Galih; , Fauzan, SE, Ak, M.Si (2016)
This study aims to determine the effect of compensation motivation and organizational commitment to employee performance to local authorities (Case Study in DPPKAD Karanganyar). This research is quantitative. The method used in collecting data in this study a questionnaire, observation, and library research (documentation) .Populasi in this study were all employees of DPPKAD Karanganyar. Testing the hypothesis in this research is the multiple linear regression analysis. Compensation results showed a positive and significant effect on employee performance shown by tcount 3,011 bigger than t table (2.013), received at the 5% significance level. Motivation positive and significant impact on employee performance shown by tcount 2,288 bigger than t table (2.013), received at the 5% significance level. Organizational Commitment positive and significant impact on employee performance shown by tcount 3.152 is greater than t table (2.013), received at the 5% significance level. Based on the test results showed Fhitung F 24.674 with p-value = 0.000, while the F table at a significance level of 5% with df = k-1 or 3-1 = 2, and DF2 = nk = or 49-3 or 49-3 = 46 is with 2.81. Therefore F count> F table (24.674> 2.81), then the regression model on the influence Compensation Motivation and Organizational Commitment Against Employee Performance Case Study On Local Government in DPPKAD Karanganyar already fit of goodness or fit. Based on the test results show the coefficient of determination R2 of 0.627 adjustedR2 This suggests that the independent variables in the model (Compensation, Motivation, Organizational Commitment,) explains the variation in the Employee Performance DPPKAD Karanganyar amounted to 62.7% and 37.3% is explained by factors or variables other outside the model.